Study of Devitrification Kinetics of Cryoprotectant Aqueous Solutions Using Thermoplastic Deformation Method - Osetsky, A. I.; Kirilyuk, A. L.; Gurina, T. M. (Problems of Cryobiology and Cryomedicine, 2005)
There was considered the method for investigating frozen solutions of cryoprotectants, cell suspensions and tissues, based on measuring their plastic deformation in the regimen of continuously increasing temperature within the range of -196…20°C at a constant external load. Using this method the devitrification temperatures Tg of aqueous solutions of such cryoprotectants as glycerol, DMSO, PEO-1500 within a wide range of concentrations were determined. For the first time Tg values within 5…15% (weight/weight) concentrations range were found-out.